The effects of 7% alcohol tinctures of echinacea purpurea on the morrhological structure of rat testes. - Sharapova, O. M. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. The search of drugs that improve the morphological condition of the testicles of humans and animals that have been subjected to the action of harmful factors of the external environment, in particular the electromagnetic field is the actual problem of modern morphology today.The authors in this study tried to investigate the effects of 7% alcohol tincture of Echinacea purpurea by identifying morphological changes in testicles of rats. Objective. The aim of the study was to determine the morphological changes in testicles of rats after using them immunomodulator - 7% alcohol tincture of Echinacea purpurea. Methods. Experimental group consisted of 35 white rats-males weighing 180-200g, control group - 6 males. Animals of the experimental group was administered intragastrically 7% alcohol tincture of Echinacea purpurea based 0,0018 mg/kg weight of the animals for five days. After the experiment the animals were euthanized by cervical dislocation, the animals were removed from the testes. Methylene blue and sodium tetraborateusedduring the manufacture of histological preparations for coloring the slices. Results. It was ascertained during the investigation that the morphological changes were taking place in the animals’ testes injected immunomodulator. Those changes slightly differed from the structure of the control animals’ testes.Tunica albuginea of testicles was of the same structure as in the testes of the animals of the control group, the cell dissemination was not observed. Convoluted seminiferous tubules are closely adjoined to each other, have rounded or oval forms. The layers of basal membrane retained its orientation, edematous effects were not observed, there was not a delamination of basal membrane. 4-5 spermatogenic epithelial layers, where germ cells at all stages of the spermatogenic cycle: spermatozoon, spermatocytes, spermatids 1, 2 order and spermatozoa are determinedon the basal membrane. The gametes at all stages development were present in greater numbers comparing with the control animals’ testicles in sight of the microscope. The large diameter average values of the rats’ tests convoluted seminiferous tubules consumed the immunomodulator increased in comparison with the animals’ control group to 0.252±0.036 mm (p<0.005). It attested the improvement in the testicles’ spermatogenic function. Conclusion. Moderate venostasis in the arterial and venous link of the testicular ovarian blood stream was observed in rats after application of Echinacea purple tincture. Mild arterial edema was manifested more than in the venous bed in the structure of the rats’ microcirculatory bed of testicles after their using of immunomodulator.